Estimating the frequency and cost of emergency department presentations and hospitalisation of chronic obstructive pulmonary disease patients: A retrospective analysis from regional Queensland. (31st October 2020) - Rana, Rezwanul; Gow, Jeff; Moloney, Clint; King, Alex; Keijzers, Gerben; Beccaria, Gavin; Mullens, Amy
Abstract: Objective: Chronic obstructive pulmonary disease (COPD) patients commonly have frequent visits to the ED. Consequently, COPD has a significant effect on total healthcare expenditure. The objective was to measure the frequency of ED presentation and hospitalisation among COPD patients and to estimate the costs resulting from such care utilisation. Methods: This was a causal‐comparative non‐experimental research design conducted in three regional hospitals between 2016 and 2018. Two different original data sets were used: an automated hospital data set and an audit of patient charts. Secondary cost data were also used. Data were analysed using Pearson's χ 2 test to estimate the relationship between several patient and treatment‐related characteristics. Results: There were 5253 patient presentations at ED and hospital length of stay data were available for 5079 COPD patients. The total cost of hospital stays was $42.14 million for the time period and the mean average cost was $8297 for ED patients who were admitted to hospital. Factors significantly associated with hospital length of stay were age and time spent in the ED. Noticeably, one (51.7%) in two COPD patients were discharged from ED (all destinations) within 4 h irrespective of their triage category. Conclusions: COPD patient presentation to ED and admission to hospital is an expensive method of providing healthcare to manage this chronic condition. Clinical practitioners and policy makers need to develop and implement optimal integrated care management systems to reduce this hospitalisation rate and reduce the societal costs associated with COPD patient management. Abstract : The objective was to measure the frequency of ED presentation and hospitalisation among COPD patients and to estimate the costs resulting from such care utilisation. COPD patient presentation to ED and admission to hospital is an expensive method of providing health care to manage this chronic condition.